Neuroprotective effects of ethyl acetate extract of Zingiber zerumbet (L.) Smith against oxidative stress on paraquat-induced parkinsonism in rats - Farah Wahida Ibrahim,; Umi Noraashikin Zainudin,; Mazlyzam Abdul Latif,; Asmah Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Zingiber zerumbet has been traditionally used as an anti-inflammation and antioxidant agent. The present study investigates the neuroprotective effects of ethyl acetate extract of Z. zerumbet against oxidative stress on paraquat (PQ)-induced Parkinsonism in rats. Forty male Sprague-Dawley rats were divided into five groups: Negative control (normal saline), positive control (N-acetylcysteine, NAC 20 mg/kg + PQ 10 mg/kg), PQ only, 200 mg/kg Z. zerumbet + PQ and 400 mg/kg Z. zerumbet + PQ. The extract was given orally for 19 consecutive days and PQ was administered intraperitoneally on day 8-12th of the treatment regime. Both serum and fresh brains containing substantia nigra (SN) region were taken for biochemical and histological analysis. Administration of both 200 and 400 mg/kg ethyl acetate Z. zerumbet extracts to the PQ-treated groups have resulted in: Decreased levels of MDA and PC in the SN homogenates; and increased SOD, GPx; and CAT activities in the SN and serum. Overall, ethyl acetate extract of Z. zerumbet reduced oxidative stress in the SN of PQ-induced neuronal damages, therefore, has the potential to be developed as a preventive agent for neurodegenerative disorders caused by environmental toxins.